EFFECT OF WORK STRESS AND WORK LOAD ON BURNOUT AND ITS IMPLEMENTATION IN TURNOVER INTENTION ERHA CLINIC BRANCH OFFICE (BOGOR, DEPOK AND MANGGA BESAR) - Saputro, Rian; Muhammad Havidz Aima; Farida Elmi (Dinasti International Journal of Management Science, 2020)
This study aims to identify and explain the effect of Job Stress and Workload against Burnout and Turnover Intention Implementation at Erha Clinic, Responden 64 employees (the whole population). Data collected through interviews and questionnaires. Data were analyzed using path analysis (software SmartPls 3.0) and correlation matrix between dimensions (software SmartPls 3.0). The results showed that: (1) Work Stress and Workload both partially and simultaneously influence the Burnout; (2) Job Stress, Workload and Burnout partially and simultaneously influence Turnover Intention; (3) Burnout Mediating Effect of Job Stress on Turnover Intention and (4) Burnout does not mediate Workload Influence on Turnover Intention. Based on the analysis of the correlation matrix between dimensions, determines the level of work stress, which has a positive correlation with the productivity of labor it is advisable to give adequate time and equipment. Workload level that have a positive correlation with Burnout it is advisable to maintain and improve the dimensions that give incentives. Meanwhile, to reduce the level Turnover Intention, which has a positive correlation with the performance it is advisable to maintain and increase the dimensions of that training